Biomarkers for febrile urinary tract infection in children - Shaikh, Nader; Kurs-Lasky, Marcia; Liu, Hui; Rajakumar, Vinod; Qureini, Heba; Conway, Isabella O.; Lee, Matthew C.; Lee, Sojin (Frontiers in Pediatrics, 2023)
ABSTRACT Background and Objectives: The current reference standard for pediatric urinary tract infection (UTI) screening is the leukocyte esterase (LE) dipstick test has suboptimal accuracy. The objective of this study was to compare the accuracy of novel urinary biomarkers to that of available markers Methods: We prospectively enrolled febrile children who were evaluated for UTI based on their presenting symptoms. We compared the accuracy of urinary biomarkers to that of accuracy of available markers (white blood cell count, LE). Results: We included 374 children (50 with UTI, 324 without UTI; ages 1 to 35 months) and examined 35 urinary biomarkers. Urinary biomarkers that best discriminated between febrile children with and without UTI were urinary Neutrophil Gelatinase Associated Lipocalin (NGAL), IL-1, CXCL1, and IL-8. Of all examined urinary biomarkers, urinary NGAL had the highest accuracy with a sensitivity of 90% (CI: 82-98) and a specificity 96% (CI: 93-98). Conclusions: Because the sensitivity of the urinary NGAL test is slightly higher than the LE test, it has the potential to reduce missed cases of UTI. Limitations with using urinary NGAL over LE include increased cost and complexity; further investigation is warranted to determine the cost-effectiveness of using urinary NGAL as a UTI screening test.